2020
DOI: 10.1016/j.optcom.2020.125742
|View full text |Cite
|
Sign up to set email alerts
|

Temporal super resolution imaging inspired by structured illumination microscopy

Abstract: In this paper, a method for increasing the temporal resolution of a temporal imaging system has been developed. Analogously to the conventional spatial imaging systems in which resolution limit is due to the finite aperture of the lens, in a temporal imaging system, finite temporal aperture of the time lens is responsible for limited temporal resolution. Based on the method used in spatial structured illumination super-resolution microscopy in spatial optics, we have utilized time prisms, which are temporal ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Therefore, our proposed concept presents an interesting alternate to a set of classical beam splitting cubes and multiple delay-lines that could be very tricky to adjust in terms of delay and amplitude. It can be one of the building block of photonic setups targeting temporal super resolution [42] or temporal holography. One may also easily extend our concept to generate pulse sequence with different amplitudes that could be further used, through cross-phase modulation, to generate multi-focal imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our proposed concept presents an interesting alternate to a set of classical beam splitting cubes and multiple delay-lines that could be very tricky to adjust in terms of delay and amplitude. It can be one of the building block of photonic setups targeting temporal super resolution [42] or temporal holography. One may also easily extend our concept to generate pulse sequence with different amplitudes that could be further used, through cross-phase modulation, to generate multi-focal imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a similar concept, the temporal resolution was defined in previous works to be the shortest transform-limited Gaussian FWHM pulse-width that we get in the output of the lens after inserting a Gaussian pulse in it 25 . Because of this resolution limitation, temporal super-resolution methods have been proposed such as a method that is based on localization microscopy algorithm 26 , time lens array imaging 27 , and a method that is inspired by structured illumination microscopy 28 .…”
Section: Fibers-based Temporal Super-resolved Imaging Sagie Asraf * mentioning
confidence: 99%
“…Indeed, the parabolic spectral phase induced by the dispersion of an ultrashort optical pulse is equivalent to the paraxial diffraction affecting the spatial propagation of a light beam [5][6][7]. This space/time duality has already been extremely fruitful and has stimulated numerous new concepts or interpretation in ultrafast optics such as temporal or spectral lenses [8,9], Fresnel lens [10], super resolution imaging [11], dispersion gratings [12] or two-wave temporal interferometers [13], to cite a few. Other studies have established links between the near-field propagation observed in diffraction and advanced applications for high repetition-rate sources when initial periodic phase modulation is converted into intensity pattern [14][15][16][17][18] in a process that can be linked to the Talbot array illuminators in the spatial domain [19].…”
Section: Introductionmentioning
confidence: 99%